2020
DOI: 10.1155/2020/5393041
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Modifies Lipid Composition of Two Cancer Cell Lines

Abstract: Resveratrol (Resv) offers health benefits in cancer and has been reported to modulate important enzymes of lipid metabolism. Studies of its effects on lipid composition in different subtypes of breast-cancer cells are scarce. Thus, we investigated the alterations in phospholipids (PL), fatty acids (FA), and lipid metabolism enzymes in two breast-cancer cell lines after Resv treatment. MCF-7 and MDA-MB-231 cells were treated with 80 and 200 μM of Resv, respectively, for 24 hours. We analyzed PL with radiolabele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…[ 145 ] Dietary polyphenols trigger the activation of AMPK in cancer cells, leading to disorders of lipid metabolism and carbohydrate metabolism, and weakening the antioxidant capacity of cancer cells. [ 146,147 ] AMPK is the important target of dietary polyphenols to inhibit cancer cell proliferation and promote apoptosis. Phosphoproteomic analysis was used to evaluate the effect of curcumin on colon cancer cells, results showed that AMPK was important molecular target for cancer intervention.…”
Section: The Ampk Pathway Targeting By Dietary Polyphenols In Cancermentioning
confidence: 99%
“…[ 145 ] Dietary polyphenols trigger the activation of AMPK in cancer cells, leading to disorders of lipid metabolism and carbohydrate metabolism, and weakening the antioxidant capacity of cancer cells. [ 146,147 ] AMPK is the important target of dietary polyphenols to inhibit cancer cell proliferation and promote apoptosis. Phosphoproteomic analysis was used to evaluate the effect of curcumin on colon cancer cells, results showed that AMPK was important molecular target for cancer intervention.…”
Section: The Ampk Pathway Targeting By Dietary Polyphenols In Cancermentioning
confidence: 99%
“…It has been reported that resveratrol-mediated lipidomic alterations can significantly affect glycerophospholipid metabolism [ 34 ]. Luciana Gomes found that phosphatidylcholine (PC) and phosphatidylethanolamine (PE) were decreased in MDA-MB-231 cells after resveratrol treatment [ 35 ]. Our study observed an increasing tendency in glycerophospholipids, including lysophosphatidylcholine (LPC) and lysophosphatidylethanolamine (LPE), as shown in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Metabolism changes are often associated with resistance to chemotherapy and therapeutic sensitivity in clinical chemotherapy. Breast cancer cells not only show significant differences in metabolism compared with healthy breast cells, but also show differences in drug resistance [233,234]. Cancer and metabolism are deeply interconnected, studies indicate that cancer evolution is associated with abnormal glucose metabolism that is related to high proliferation, metastasis and clinical characteristics and is allied to the action of a particular drug.…”
Section: Metabolites and Breast Cancer Patientsmentioning
confidence: 99%
“…Cancer and metabolism are deeply interconnected, studies indicate that cancer evolution is associated with abnormal glucose metabolism that is related to high proliferation, metastasis and clinical characteristics and is allied to the action of a particular drug. In this context, chemoresistance enables cancer cells to survive drug action and proliferate uncontrollably, which may lead to strong metastatic potential and cancer progression [230][231][232][233][234].…”
Section: Metabolites and Breast Cancer Patientsmentioning
confidence: 99%